AN EXAMINATION OF COMPETITIVENESS OF RURAL DESTINATIONS FROM THE SUPPLY SIDE PERSPECTIVE - Dunja Demirović; Marko D. Petrović; Luis Carlos Neto Monteiro; Stefan Stjepanović (Zbornik Radova: Geografski institut "Jovan Cvijić", 2016)
Tourist destinations are now faced with increased competition at the market and holders of tourist policy and offers have realized that understanding the factors that contribute to a better positioning in the market place, and therefore the competitiveness, is of crucial importance for further development. The aim of this paper is to determine how much Vojvodina is competitive as a rural tourism destination, and to assess the current state of all the factors that affect/could affect the competitiveness of rural tourism destinations in Vojvodina Province (Northern Serbia). The total of 136 tourism experts were interviewed, and we concluded that the key resources and attraction of rural areas in Vojvodina are rated better than the macro and industry-related factors. This suggests that a rural development strategy should have a special bond with resources and attractions of the destination, that priority should be given to maintaining all aspects of safety and security, continuous improvement of services, diversity of culinary products, as well as the application of the principles of sustainability in environmental management. The work of national and provincial institutions should have the aim to ensure that the destination has a clear idea of where it is going and what it takes to become successful in the long term.